Evaluation and Management of Suspected Sepsis and Septic Shock in Adult Patients - Tona, Azwar Iwan (Journal of Society Medicine, 2025)
Sepsis is a life-threatening clinical syndrome arising from a dysregulated host response to infection, encompassing a continuum of severity that ranges from sepsis to septic shock. Despite advances in critical care, sepsis remains a leading cause of morbidity and mortality worldwide, with reported mortality rates exceeding 10% in sepsis and rising beyond 40% when septic shock develops. Contemporary management strategies emphasize early recognition, prompt source control, timely administration of antimicrobial therapy, and hemodynamic optimization. Current clinical practice largely aligns with the definitions proposed by the Society of Critical Care Medicine and the European Society of Intensive Care Medicine, which focus on organ dysfunction as a central feature of sepsis. However, these definitions are not universally adopted, as alternative frameworks, including earlier systemic inflammatory response–based criteria, continue to influence clinical and regulatory practices in certain settings. The ongoing debate highlights concerns that the broad application of modern definitions may inadvertently promote overtreatment, particularly unnecessary exposure to broad-spectrum antibiotics, in patients with less severe disease. This review summarizes contemporary concepts in the clinical management of sepsis and septic shock, integrating evolving definitions with practical and bedside decision-making. Emphasis is placed on balancing rapid, protocolized care for high-risk patients with judicious therapeutic strategies to minimize harm to patients with milder presentations. By synthesizing guideline-based recommendations and ongoing controversies, this review aimed to provide a pragmatic framework for clinicians managing sepsis in diverse clinical contexts.